Hepatoprotective Effects of Fumaria parviflora L. on CCl4-induced hepatotoxicity - A Jamshidzadeh; H Nikmahad (Institue of Medicinal Plants, ACECR, 2006)
Background: Liver, the largest internal organ in the body, plays a central role in many essential physiologic processes and has numerous functions. Nevertheless, its disorders are many fold. Hepatic disease may result from a variety of therapeutic drugs or toxins that cause wide hepatic lesions. Objective: From the old times, plants have been used for the treatment of liver disorders. In this study, protective effect of hydroalcoholic extract of Fumaria parviflora L was determined. Methods: Male rats were used in this study. In the test groups, they received l00, 200 and 300mg/kg of the extract, alone or with CCl4 (3ml/kg). The liver function test and hystopathological observations were performed for all groups. Results: Carbon tetrachloride caused sever liver damage and the extract of the plant with doses higher than l00mg/kg prevented CCl4-induced liver damage Conclusion: The results of the present study support the traditional beliefs on hepatoprotective effects of Fumaria parviflora